On common ground world religions in America - Eck, Diana L. (New York : Columbia University Press, 2002)
Explores the history, beliefs, and current practices of fifteen religious traditions in the United States
System requirements : Windows 95,98,2000/166MHZ Intel Pentium procesor or greater /640x480 16 bit (High color) Display/4x CD-ROM drive/32 MB or more installed RAM/16 bit sound card with speakers or headphones ; Macintosh : OS 8.1 or later (OS x running in'Classic mode' only)/640 x 480 16-bit (Thousands of colors) Display / 4x CD-ROM drive/32 MB or more of installed RAM
Keywords: Religious pluralism -- United States -- Interactive multimedia; United States -- Religion -- 1960- -- Interactive multimedia